Efeito do α-felandreno complexado e não complexado em hidroxipropil-β-ciclodextrina na nocicepção orofacial em roedores - Machado, Brennda Gonzaga (2022)
Objective: the work aims to expand the studies involving the pharmacological effects of the αphelandrene monoterpene, specifically in the promotion of orofacial antinociception. Methods: a hydroxypropil-β-cyclodextrin (HPβ-CD) complex was prepared with incorporation of the α-felandorene that was later physically characterized through high efficiency liquid chromatography (CLAE) and differential exploratory calorimetry (DSC). Seeking to evaluate the possible analgesic action of α-felandreno in animal models in orofacial nociception, the animals were divided into four groups (n = 8 per group) and treated with unlapled α-felandreno (FEN) at the 50mg/kg oral dose , α-felandreno complex in hydroxipropil-β-cyclodextrin (FENHPβCD) at a dose of 50mg/kg oral via, negative control (tween 80 0.2% in water) 10ml/kg per gavage and positive controls (morphine 10mg/kg i.p. For tests of formaline, glutamate and hypertonic saline; camphor 7.6mg/kg i.p. for the scine test and, diazepam 3mg/kg i.p. for the rod rod test). Finally, quantification of TNF-α and IL-1β cytokines was made in the Vibrissa region after the formaline test and animal locomotor analysis analysis through the motor coordination test and data collection for statistical evaluations. Results: in the α-felandorereno quantification test by Clae, a 5.8 minutes retention time was found and a peak of good chromatographic resolution, the correlation coefficient R2 = 0.9998 proves the linearity of the method and the limit results Detection (LD) and quantification (LQ) (0.81 and 2.44 µg/mL, respectively) demonstrated the sensitivity of the method. DSC results indicated greater α-felandreno stability when incorporated into HPβ-CD. In formalin-induced nociception, a significant antinociceptive effect was observed in animals treated with FEN and FEN-HPβCD 50mg/kg when compared with the vehicle in both the neurogenic (p<0.001 for both) and inflammatory (p<0.001 and p<005, respectively) phases, parallel to this, there was an inhibition of the cytokines TNF-α (p<0.05 and p<0.01, respectively) and IL-1β (p<0.01 and p<0.05, respectively). The treatment with FEN and FEN-HPβCD 50mg/kg when compared to the vehicle significantly reduced the nociception induced by cinnamaldehyde (p<0.01 and p<0.001, respectively), glutamate (p<0.001 and p<0.01, respectively) and hypertonic saline (p<0.05). In the motor coordination test done through the Rota-Rod apparatus, no behaviors were observed that influenced the locomotor activity of rodents, as animals treated with Fen and FEN-HPβCD 50mg/kg remained in the bar for more than 170 seconds in Every time (30, 60 and 120 minutes). Conclusion: it can then be concluded that α-felandorene monoterpene has antinociceptive effect, probably involving TRPA1, TRPA1, glutamatergic receptors and release of TNF-α and IL-1β cytokines.